Psychoeducation of Emotion Management Skills through Expressive Writing for Darul Falah Integrated Middle School Students - Hernanda, Adella Trifanny (Jurnal Graha Pengabdian, 2023)
Emotion management is something that is needed in junior high school students because at that age students are in a phase of emotional instability. With good emotion management skills, the individual can change negative emotions into more positive reactions. Therefore, the expressive writing technique is an option for emotional management which aims to make emotional responses bring positive responses. With this psychoeducation, it is hoped that Darul Falah Junior High School students can manage emotions well by using the expressive writing method in managing emotions so that they do not give rise to negative responses.